Development of economical maximum power point tracking system for solar cell - Rashid, Muhammad Mahbubur; Muhida, Riza; Alam, A. H. M. Zahirul; Habib Ullah, Mohammad; Kasemi, Banna (INSI Publications, 2011)
Photovoltaic (PV) power generation system operates under various isolation conditions, which may generate several maximum output power points on the I-V curve of the PV array and raises serious problem on Maximum Power Point Tracking (MPPT) control of the system. This research concerned the design of MPPT for photovoltaic system by using PIC controller. A MPPT unit is developed for the optimum coupling of a Photovoltaic Panel (PVP) to the battery (load)through a controlled Buck type dc-dc converter which has made the difference from the past MPPT techniques and made it cost effective. The system has high-efficiency, lower-cost and low-power consumption. Moreover it permits easy modifications. This system operates at its maximum power generation with increasing the PV output power by as much as 32-36%. This study includes the theoretical aspects and experimental results of the proposed method.